MODEL PEMBELAJARAN MANAJEMEN PROYEK SISTEM INFORMASI (MPSI) BERBASIS APK PADA STMIK NURDIN HAMZAH - J, Riswan (JURNAL AKADEMIKA, 2017)
The research and development of this learning model aims to develop the APK model of the practical Information Systems Management (MPSI) lecture program, as a complement to the manual lecturing process conducted at STMIK Nurdin Hamzah. The APK model provides a learning menu consisting of Home content, MPSI Courses, Classroom Improvement Materials, Pre-Class Materials, Online Course. Each of these content consists of several sub-materials that describe the course material that will be studied by the students. Students can download APPS application of this MPSI, and to be able to use all facilities in this APK application, the student must first register as user of this application. Each student who signed up will get a username and password. This APK application has been utilized by students in the course subjects of MPSI, students give a positive response to this APK application. This APK application can be a prototype for other subjects.   Keywords : Learning Model, Convensional Learning, online Learning, APK